Determinants of preeclampsia among pregnant woman in Bantul - Jonri Maringan Pandiangan; Hari Kusnanto (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Determinants of preeclampsia among pregnant woman in BantulPurposeThis study aimed to determine the factors associated with the incidence of preeclampsia in pregnant women in Bantul district. MethodsThis research was a non-experimental study with quantitative approach. The study used a case control design with a ratio of 1:2. Case were pregnant women with preeclampsia in 2015 and control were pregnant women who did not suffer preeclampsia. we used total sample and there is 116 women with pre-eclampsia. The variables studied were age, parity, body mass index, antenatal care, pregnancy range and maternal education interval. We used chi square and logistic regression tests. Results We got 107 cases and 247 controls. Multivariate results showed that the factors associated with the incidence of preeclampsia were body mass index (OR=3.69, 2.00-7.07) and maternal age over 35 years (OR=2.18, 1.24-3.85). ConclusionThis study found that body mass index is a risk factor for preeclampsia of pregnant women. Routine surveillance of maternal risk factors in monitoring of local area on maternal and child health may be used to detect the incidence of preeclampsia in the remaining pregnancy.